ANGIOSPERMS SPECIES DIVERSITY IN BIOLOGICAL GARDEN SEUNGKO MULAT - Eva Nauli Taib; Cut Ratna Dewi (Bioma : Jurnal Ilmiah Biologi, 2013)
Biological gardens Seungko Mulat is an area in Aceh Besar district Lhoong that have different types of plants in vegetation dominance by species of Angiosperm. This study aims to determine the kinds and diversity of plants Angiosperm contained in the biological garden Seungko Mulat Lhoong Aceh Besar district. The research was carried out in the biological garden of Seungko Mulat used exploratory survey method for this kind of tree, as well as squares method for herbs and shrubs. Analysis of the data by calculating the index of diversity and importance value. The results showed that in the study area, there are 9 species Angiosperm that herbs, 13 species of shrubs and 10 species of trees. The most dominant type of Angiospermae is Paspalum conjugatum, Mimosa pudica, Eupatorium oderatum and Etlingera littoralis. Index Angiosperm species diversity is low to moderate for herbs and shrubs. The necessity for herbs are 92.54 and 69.22 for the bush.Keywords: Diversity, Angiospremae, Seungko Mulat